(untitled) (PANGEEA, 2025)
The paper presents the construction of a model to simulate runoff on the Nicolina River through the non-permanent accumulation Ciurea, Iaşi County. HEC-RAS 2D software was used to create a hydraulic model with detailed two-dimensional unsteady flow river hydraulics calculations on the channel and floodplain. Gridded terrain data and a land cover data layer in the RAS Mapper module were used to associate with a specific geometry input file and a specific results output file. The storage area of the basin was defined by an elevation-volume curve. Boundary conditions were set as outflows from Ciurbeşti and Ezăreni reservoirs, situated on the tributaries and a downstream flow measured at Iași hydrometric station. The simulated event was the flood corresponding to a near 10% probability of exceedance, produced on the River Nicolina in July 2013. HEC-RAS 2D software generates results in two-dimensional hydraulic files that illustrate the flow, speed, water level, and spatial extent of flooded areas. The two-dimensional model is calibrated with reference terms of the measured water level in the modeled area and the maximum historical flood level recorded by physical landmarks.